Wife Abuse and Its Affecting Factors among the Married Woman - Hassan Shams-Esfandabad; Sousan Emami-Pour; Seyyed Jalal Sadrosadat (University of Social Welfare and Rehabilitation Sciences, 2004)
Objective: The incindence of wife abuse and its impacts on psychological as well as physical health of the women and in its ultimate negative effects on the health of the family have been presented in many researches. The purpose of the present study was to investigate physical and psychological wife abuse among the married women living in Tehran. Materials & Methods: Study sample (N=1000) consisted of two group of married women (18-45 years): those who did not refere to domestic curts (n= 800), and those who had problem with their husbands and therefore refered to domestic curts (n=200). Moffir et al. (15) Questionnaire has been applied. Results: Data analysis revealed that: psychological and physical wife abuse among subjects in the first group were 87/9 and 47/9 respectively. Psychological and physical wife abuse among subjects in the second group were 99/5 and 91 respectively. Wife abuse was significantly related to the age of the couples and duration of their marriage the older the couples and the longer the marriage, the higher the wife abuse. There was a significant negative relationship between education of the couples and wife abuse. The higher the education, the lesser the wife abuse. Those husbands who consumed alcohol or drug, abused their wives significantly more than those husbands who did not consume alcohol or drug. Husbands with psychological problems abused their wives significantly more than husbands without psychological problems. Psychological and physical wife abuse among the subjects in the second group were higher than psychological and physical wife abuse among the subjects in the first group. Conclusion: Our findings suggested that there are relationships among the variables of age, education, alcohol or drug consumption, husbands psychological disorders and wife abuse. Legislation of a low wich forbids husbands to abuse their wives and increament of the general knowledge about wife abuse by means of mass media may have significant effects on reduction of wife abuse.